2021
DOI: 10.3389/fsufs.2021.611089
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' Sources and Varieties of Cassava Planting Materials in Coastal Kenya

Abstract: Cassava (Manihot esculenta Crantz) grows in diverse agro-ecological zones. In Kenya, it is widely cultivated in Western and Coastal regions. It is mainly grown for food and nutrition security and excess roots are sold to generate income for the farm households. Its productivity per unit of the land area is high compared to maize and wheat which are staple crops in the country. However, scarcity of cassava planting materials and pests and diseases limit production in these regions. This study aimed at revealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Most of the farmers in the area under study had farm sizes of ranging from 2 to 5 ha, indicating that majority of the respondents were small-scale farmers. The area under cassava production on average was ranging from 0.5 to 1 ha as reported by 39.2% of respondents and this in agreement with previous reports by Chikoti et al (2016) and Kidasi et al (2021). Therefore, for farmers to realize the benefits of high cassava productivity and utilization potential, there is need to promote large-scale cultivation of cassava in many cassava-growing regions (Shirima et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…Most of the farmers in the area under study had farm sizes of ranging from 2 to 5 ha, indicating that majority of the respondents were small-scale farmers. The area under cassava production on average was ranging from 0.5 to 1 ha as reported by 39.2% of respondents and this in agreement with previous reports by Chikoti et al (2016) and Kidasi et al (2021). Therefore, for farmers to realize the benefits of high cassava productivity and utilization potential, there is need to promote large-scale cultivation of cassava in many cassava-growing regions (Shirima et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…However, we could observe that, for example, a consistent number of fields in the cluster 1 were located a bit far from main roads/rails than fields from cluster 2. Such distant location pattern of cassava fields could narrow the possibilities in the sourcing of cuttings since the transportation of vegetative material over long distances can be a serious limit for the farmer as seen in the literature (El-sharkawy, 2004;Mdenye et al, 2016;Kidasi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A similar study in Rwanda indicated that majority (76.9%) of the farmers obtain cuttings for free from either their own fields or from neighbors (Nyirakanani et al, 2021). In Kenya, majority of farmers (83%) recycled planting materials from the previous crop while some 67% obtained the planting material from their neighbors (Kidasi et al, 2021). In the absence of a formal seed system, planting material traded or supplied often suffers from a lack of quality control, farmers are more likely to plant virus-infected cuttings, which can lead to low yield.…”
Section: Seed Systems and Disease-free Planting Materialsmentioning
confidence: 92%
“…Cassava seed systems in Africa are largely farmer driven with low seed quality controls. Re-use of the farmer's own seed supply remains the most common source of seed (Kidasi et al, 2021;Szyniszewska et al, 2021).…”
Section: Seed Systems and Disease-free Planting Materialsmentioning
confidence: 99%